The model of younger children spiritual and moral values formation in modern family conditions - Kadol, Fedor V.; Siarheyenka, Tatsiana E. (Journal of the Belarusian State University. Journalism, 2019)
One of the priorities of modern pedagogics – the process of younger generation spiritual and moral education is presented. The authors attempted to create the model of spiritual and moral values formation of younger schoolchildren in pedagogical interaction of family and educational institutions. Extra attention is paid to the influence of the family on spiritual and moral values formation of schoolchildren. The principles and methods of spiritual and moral education are revealed.